Digital Feminisms and the Split Subject: Short-circuits through Lacan’s Four Discourses - Horbury, Alison (CM: Communication and Media, 2016)
This paper takes the emergent field of digital feminisms as a case for thinking about the ways in which Jacques Lacan’s theory of the four discourses – that of the master, hysteric, university, and analyst – can contribute to our understanding of the subject in digitally mediated communications. Lacan’s theory is useful in articulating the relationship between the feminist subject, knowledge production, and the modes of enjoyment that structure speech particularly where feminist discourses are animated in digital communications. As a protest discourse, feminist discourse has been equated with the productive discourse of the hysteric, but once institutionalized, I argue, it takes on the structure of the university discourse, bypassing the critical phase of the analyst. Digital feminisms offer a particularly reflective case for understanding this structural shift as, with no gatekeepers, nothing impedes the personal becoming political in digitally mediated spaces. Here, the structure of feminist discourses is amplified, exposing the dynamic affects in different discursive positions that obfuscate communication and make ‘true dialogue’ problematic. Drawing on Lacan’s theory of the four discourses, I map some of these affects as digital feminist discourses shift into the position of knowledge (what Lacan calls S2), where they are divided – cut off from their own experience and enjoyment – and positioned to address the jouissance of the Other. In this, I hope to show how Lacan’s theory of discourse offers a means of understanding the frustrations felt in much digitally mediated communication.